The effect of intravenous flumazenil on interictal electroencephalographic epileptic activity: results of a placebo-controlled study. Issue 4 (April 1991) - Hart, Y M; Meinardi, H; Sander, J W; Nutt, D J; Shorvon, S D
Abstract : The effect on interictal electroencephalographic epileptic activity of intravenous flumazenil (Ro 15-1788), a benzodiazepine antagonist and potential antiepileptic drug, was studied in 10 patients. Comparison was made with intravenous diazepam (10 mg) and placebo using a single-blind, single-dose, cross-over design. A dose of 3 mg flumazenil was well tolerated and produced a significantly greater reduction in the number of epileptic transients during the first 40 minutes after injection than did placebo (p less than 0.05). This effect was similar to that of diazepam in magnitude and duration. When flumazenil (3 mg) was administered immediately after intravenous diazepam (10 mg), the reduction in interictal epileptic activity was not significantly different from that produced by diazepam alone. The results suggest that either flumazenil has intrinsic antiepileptic activity and in this respect acts as a partial agonist at the benzodiazepine receptor, or that it is antagonising an endogenous proconvulsant ligand in these patients.